P269 LOCAL ULTRASOUND–FACILITATED THROMBOLYSIS IN ACUTE PULMONARY EMBOLISM: HAS A SPACE?. (18th May 2022) - Camassa, N; Liguori, M; Pansini, M; Troccoli, R; Carretta, D; Dachille, A; Giardinelli, F; Signore, N; D'agostino, C
Abstract: Acute pulmonary embolism (PE) has an annual incidence of 48 patients per 100, 000 with a mortality rate of 10%, few hours after the onset of symptoms. The use of full dose of thrombolytic agent is currently the treatment of choice in acute PE at intermediate and high risk, although its contraindications are well known. An alternative choice is delivered, via percutaneous femoral or jugular venous access, infusion catheters in the pulmonary artery (PA), in order to perform a local thrombolysis (based on a map of thrombus distribution observed at pulmonary CT), with a lower dose of trobolytic agent (rTPA) in a limited time, with a core for emission of ultrasound waves capable of breaking the mesh of the thrombus. Data from the KNOCOUT PE registry show a reduced frequency of fatal intracranial hemorrhage (ICH 2.5%), compared with the full dose of rTPA. Since February 2021 we have treated 7 patients with PE, all with cTnI, D–dimer and high NT–ProBNP and with pulmonary CT finding of large thrombus burden with pruning of peripheral pulmonary branches compatible with the diagnosis of PE at high and intermediate risk in patients with complex comorbidities (significant PESI and simplified PESI). On admission to the ICU all patients were with BP < 100 mmHg, RR > 20/min, satO2 < 90% and HR > 100 bpm. In echocardiogram all were with impaired RV (RV/LF ratio >1 and TAPSE <15mm). All patients was treated with UHF, 1 in fondaparinux for thrombocytopenia. At time between 4h and 8gg from the onset of symptoms, all patients underwent placement of 1 or 2 catheters in right and/or left PA, 106 cm and 135 cm length with zone of interest between 18/32 cm. When possible, hemodynamic parameters were evaluated: PAPm, cardiac output, and stroke volume to characterize the associated hemodynamic deterioration. 12mg of rtPA per catheter was administered over 12 hours. In 3 patients an echocardiogram was performed at 6 hours. In all at 24 hours, vital and laboratory parameters were measured, and in one patient, right heart catheterization was repeated. In no patient was treatment discontinued early, nor were ICH or minor bleeding recorded. Low dose of rtPA allowed use of the technique in patients with severe comorbidities at the limit of thrombolysis use, in the presence of marked RV distress and severe hemodynamic instability. Trials are in progress to shorten the time and therefore reduce the dose of rTPA with equal effectiveness on the clinical course of acute PE.